2019
DOI: 10.7150/ijbs.34718
|View full text |Cite
|
Sign up to set email alerts
|

PAK4 Regulates Actin and Microtubule Dynamics during Meiotic Maturation in Mouse Oocyte

Abstract: Meiotic maturation of oocyte is an important process for successful fertilization, in which cytoskeletal integrality takes a significant role. The p-21 activated kinases (PAKs) belong to serine/threonine kinases that affect wide range of processes that are crucial for cell motility, survival, cell cycle, and proliferation. In this study, we used a highly selective inhibitor of PAK4, PF-3758309, to investigate the functions of PAK4 during meiotic maturation of mouse oocytes. We found that PAK4 inhibition result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The PAK family consists of six members, PAK1 to PAK6 [24]. PAK1, PAK2, and PAK4 have been reported to exist in mammalian oocytes [15,25]. In the current study, we identified that activated PAK1 exhibited a dynamic distribution and expression during meiosis in porcine oocytes.…”
Section: Discussionmentioning
confidence: 51%
“…The PAK family consists of six members, PAK1 to PAK6 [24]. PAK1, PAK2, and PAK4 have been reported to exist in mammalian oocytes [15,25]. In the current study, we identified that activated PAK1 exhibited a dynamic distribution and expression during meiosis in porcine oocytes.…”
Section: Discussionmentioning
confidence: 51%
“…The migration and positioning of the meiotic spindle at the cortex of the oocyte are crucial for asymmetric division, with actin microfilaments assuming a vital role in spindle migration [ 15 , 16 ]. As the meiotic spindle forms near the center of the cell, actin microfilaments accumulate around the periphery of the spindle and form actin flows, which facilitate spindle migration from the center to the cortex [ 17 ]. Actin filaments, initially evenly distributed in the oocyte cortex, become polarized during spindle migration.…”
Section: Introductionmentioning
confidence: 99%
“…High quality oocytes are essential for successful fertilization, early embryo survival and healthy fetal development [3]. However, many defects can damage oocyte maturation, including oxidative stress, apoptosis, endoplasmic reticulum (ER) stress and mitochondrial dysfunction [4][5][6]. Thus, the quality of oocytes is the major determinant of female reproductive potential.…”
Section: Introductionmentioning
confidence: 99%